New Insight into Glabellar Arteries: A Three-Dimensional Computed Tomography and Dissection Study. Issue 5 (19th December 2022) - Liao, Zhi-Feng; Cong, Li-Yao; Luo, Cheng-En; Zhan, Wen-Feng; Luo, Sheng-Kang
Abstract : Background: Vascular complications from glabellar intravascular filler injections are major safety concerns. Filler injection into the glabella without precise knowledge of its vascular topography poses a risk of severe complications. Methods: Computed tomography was used to study 90 cadaveric heads after contrast agent and filler injection, and 15 cadaveric heads were dissected. Results: Central (CAs), paracentral (PCAs), and reverse dorsal nasal arteries (rDNAs) were found in 70 (38.9%), 58 (32.2%), and 16 (8.9%) of the 180 hemifaces, respectively. Based on the presence of CAs, PCAs, and rDNAs between the bilateral supratrochlear arteries (STAs), glabellar arteries were categorized into two main patterns: in type 1 [without named arteries between bilateral STAs; 22 of 90 (24.4%)], the glabella was supplied by bilateral STAs and their branches; in type 2 [with named arteries between bilateral STAs; 68 of 90 (75.6%)], the glabella was supplied by bilateral STAs and CAs, PCAs, and rDNAs. Type 2 could be further divided into three subtypes: in type 2a [45 of 90 (50.0%)], the glabella was supplied by bilateral STAs and one of the named arteries; in type 2b [21 of 90 (23.3%)], the glabella was supplied by bilateral STAs and two of the named arteries; and in type 2c [two of 90 (2.3%)], the glabella was supplied by bilateral STAs and unilateral CA, PCA, and rDNA. Conclusion: This study elucidated novel arterial systems and proposed considerations for glabellar filler injection.